Storytelling as a Tool for Teaching Tolerance: A Cross-Cultural Case Study in Multicultural Schools - Arum Putri Rahayu; Ethan Tan; Ryan Teo; Kaito Tanaka (International Journal of Educational Narratives, 2025)
Background. Promoting tolerance and intercultural understanding has become an essential goal in multicultural education, where diverse values, beliefs, and worldviews coexist in classroom settings. Storytelling, as a pedagogical tool, holds significant potential to foster empathy and social cohesion among students from different cultural backgrounds. Purpose. This study aims to explore how storytelling enhances students’ attitudes toward tolerance and mutual respect in multicultural schools. Using a qualitative cross-cultural case study design, data were collected through classroom observations, semi-structured interviews, and reflective journals involving teachers and students from three culturally diverse schools in Indonesia, Malaysia, and Finland. Method. Thematic analysis revealed that storytelling provided a safe dialogic space for students to express cultural identity, challenge stereotypes, and build emotional connections with peers. Teachers reported that narrative-based activities encouraged perspective-taking, compassion, and openness to difference. Results. The results demonstrate that storytelling functions not only as a language or cultural learning strategy but also as a moral-educational practice that nurtures inclusive classroom communities. Conclusion. The study concludes that integrating storytelling into school curricula offers a transformative approach to cultivating tolerance and intercultural empathy in multicultural education.